2019
DOI: 10.1080/21691401.2018.1559175
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of hesperidin nanoparticles loaded by poly lactic co-Glycolic acid for improved therapeutic efficiency and cytotoxicity

Abstract: Hesperidin, as a flavonone, is recognized as promising anti-inflammatory, antioxidant, and anticancer agent. Its poor bioavailability is crucial bottleneck for therapeutic efficacy. To enhance the stability and bioactive potentials, hesperidin-PLGA-Poloxamer 407 was successfully prepared to minimize or overcome problems associated with hesperidin absorption. The characteristics of nanohesperidin were testing by in vitro dissolution study, XRD, FTIR, PSA and SEM. Antioxidant effects of nanohesperidin were studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(39 citation statements)
references
References 47 publications
3
36
0
Order By: Relevance
“…The C=O stretch recorded for the polymer at 1750 cm -1 did not change in CNPs while the peak representing the C-O ester stretching slightly moved from 1088 cm -1 for the polymer to 1078 cm -1 and 1083 cm -1 for both molybdenum halide CNPs with a P/C ratio of 2.5, TBA 2 and CMB, respectively. The vibration corresponding to the sp3 C-H stretching was detected at 2914 cm -1 for the polymer and moved significantly between 2921 and 2924 cm -1 for all CNPs tested, indicating the existence of interactions between the polymer and the or hesperidin where authors concluded to the lack (Jang et al, 2019;Gaoncar et al, 2017) or to minor (Ali et al, 2019) chemical interaction between drug and polymer.…”
Section: Nanoparticles Formulation and Characterizationmentioning
confidence: 90%
“…The C=O stretch recorded for the polymer at 1750 cm -1 did not change in CNPs while the peak representing the C-O ester stretching slightly moved from 1088 cm -1 for the polymer to 1078 cm -1 and 1083 cm -1 for both molybdenum halide CNPs with a P/C ratio of 2.5, TBA 2 and CMB, respectively. The vibration corresponding to the sp3 C-H stretching was detected at 2914 cm -1 for the polymer and moved significantly between 2921 and 2924 cm -1 for all CNPs tested, indicating the existence of interactions between the polymer and the or hesperidin where authors concluded to the lack (Jang et al, 2019;Gaoncar et al, 2017) or to minor (Ali et al, 2019) chemical interaction between drug and polymer.…”
Section: Nanoparticles Formulation and Characterizationmentioning
confidence: 90%
“…Furthermore, AuNPs have the properties of being bio-compatible and non-toxic, making them preferable drug carriers 53 . Previous investigations revealed that Hsp exerts remarkable cytotoxicity towards selected human cancer cell lines such as those of the cervix, liver, larynx, and breast 23,54 . Moreover, it was demonstrated that Hsp exerts chemo-preventive activities along with apoptotic impacts that lead to the inhibition of colon carcinogenesis in mice 55 .…”
Section: Zeta Potential Analysis and Particle Size Analysismentioning
confidence: 99%
“…Hemolysis test. Hemolysis test was performed for the prepared Hsp, AuNPs and Hsp-AuNPs samples based on a previously described method 23 , with some modifications. Briefly, whole blood (100 µL) was mixed with PBS (700 µL) and 100 µL of Hsp, AuNPs or Hsp-AuNPs at five concentrations (20,80,160,240 and 320 µg mL −1 ) were added; phosphate buffer saline served as a negative control (0% hemolysis), whereas deionized distilled water served as a positive control (100% hemolysis).…”
mentioning
confidence: 99%
“…The SEM image showed the interaction between alumina NPs and bacterial cells, clearly indicating the change in cell morphology and the aggregated particles on the cell wall. The aluminainteracted cells showed distorted cell morphology, indicating the distortion of bacterial cells [26]. Also, Murdock et al [27] observed that the behavior of alumina NPs was also influenced by particle size, shape and charge of surface.…”
Section: Wound Healing Activity By Al 2 O 3 Nanoparticlesmentioning
confidence: 99%